اسلامی قرطبہ کی تعلیمی سرگرمیاں اور جامع مسجد قرطبہ کا کردار - ڈاکٹر اکرام الحق یٰسین (FIKR-O NAZAR فکر ونظر, 2011)
The modern spainish city Cordova was once the Capital Of Islamic Caliphet (773-1232 A.D.). It palyed a great role in the promotion of culture and education as well. No other city in Europe competed it niether in education nor in materialistic advancement throughout the centuries. Many facilites for education were introduced over there, some of them for the first time in the history of Europe. For example special institutions were established to educate the people without any discrimination of colour, race, language and religion. The Great Mosque of Cardova was prominent centre of education. It worked as a board for education, a university for higher studies and a centre for debates. Facilities for education included the board and lodging for the students, arrangments for lightening and the educational halls and hostels, production of ink and writing materials, production of paper etc. Eminent scholars like Ibn-e-Rushd, Ibn-e-Arabi, Musa bin Maimun, Ibn-e-Hazam are the product of Cordova educational movement associated with the Mosque.